Incidence of genital abnormalities in beef cows of Rio Grande do Sul - Santiago, Cezar; Barros, Severo Sales de (Pesquisa Agropecuaria Brasileira, 2014)
Examination of 1,334 non-lactating beef cows, all of which had been vaccinated for brucellosis at 6 to 8 months of age, revealed that 62 of the cows were not pregnant. These open cows were slaughtered and macroscopic and histo-pathological examinations were made of the genital organs. Examinations were not made for vibriosis and trichomonosis. Twenty of the 62 cows showed genital abnormalities which could have interfered with fertility. The authors concluded that genital abnormalities play a secondary role in bovine infertility in controlled herds.